Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1093/carcin/20.10.1963
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of benzidine and its metabolites by cDNA-expressed human UDP-glucuronosyltransferases and pH stability of glucuronides

Abstract: Although glucuronidation is considered a necessary step in aromatic amine-induced bladder cancer, the specific enzymes involved are not known. This study assessed the capacity of five different human recombinant UDP-glucuronosyltransferases expressed in COS-1 cells to glucuronidate benzidine, its metabolites and 4-aminobiphenyl. [(14)C]UDP-glucuronic acid was used as co-substrate. UGT1A1, UGT1A4 and UGT1A9 each metabolized all of the aromatic amines. UGT1A9 exhibited the highest relative rates of metabolism wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…Unfortunately, we could not examine clearly the contribution of UGT1A3 isoform to the AFQ N-glucuronidation in human jejunum microsomes due to the absence of specific substrates or inhibitors for UGT1A3. It has been reported that primary amine glucuronidation was seen with UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A8, UGT1A9, and UGT2B7 Ciotti et al, 1999;Hiller et al, 1999;Kaivosaari et al, 2002). The present results were almost consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, we could not examine clearly the contribution of UGT1A3 isoform to the AFQ N-glucuronidation in human jejunum microsomes due to the absence of specific substrates or inhibitors for UGT1A3. It has been reported that primary amine glucuronidation was seen with UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT1A8, UGT1A9, and UGT2B7 Ciotti et al, 1999;Hiller et al, 1999;Kaivosaari et al, 2002). The present results were almost consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…We were unable to detect desloratadine N-glucuronide or 3-hydroxydesloratadine N-glucuronide by LC-MS/MS in our previous study (Kazmi et al, 2015). Instability is a characteristic property of certain N-glucuronides (Ciotti et al, 1999).…”
Section: Introductionmentioning
confidence: 77%
“…These glucuronides appear to be very unstable, which is a characteristic of certain other N-glucuronides (Ciotti et al, 1999). Despite this limitation, the identification of CYP2C8 in combination with UGT2B10 in the formation of 3-hydroxydesloratadine contributes to our understanding of the long-standing mystery surrounding the enzymology of 3-hydroxydesloratadine formation in humans, providing a pathway for future investigation of the genetic basis for the desloratadine poor metabolizer phenotype.…”
Section: Discussionmentioning
confidence: 99%